1986
DOI: 10.1002/cne.902510303
|View full text |Cite
|
Sign up to set email alerts
|

Topographic representation of lower and upper teeth within the trigeminal sensory nuclei of adult cat as demonstrated by the transganglionic transport of horseradish peroxidase

Abstract: Transganglionic transport of horseradish peroxidase-wheat germ agglutinin conjugate (HRP-WGA) entrapped in hypoallergenic polyacrylamide gel was used to study the patterns of termination of primary afferents that innervate the lower and upper tooth pulps within the trigeminal sensory nuclear complex (TSNC). HRP injections were made into the inferior and superior alveolar nerves in order to compare the central projections of the whole nerve with those from tooth pulps. In addition, the relationship between the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
24
0
1

Year Published

1996
1996
1998
1998

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 93 publications
(27 citation statements)
references
References 56 publications
2
24
0
1
Order By: Relevance
“…This suggests that a considerable proportion of the trigeminal primary nociceptive projection, especially from the intraoral structures, is directed to the relay nuclei located in the rostral subdivisions of the BSTC. This idea is supported by the fact that a large proportion of central projection of presumed primary nociceptors innvervating the tooth pulp is directed to rostral subdivisions of the BSTC (Arvidsson and Gobel, 1981;Westrum et al, 1981;Marfurt and Turner, 1984;Shigenaga et al, 1986bShigenaga et al, , 1989Takemura et al, 1991;Sugimoto and Takemura, 1993).…”
Section: Cgrp-ir Primary Afferent Projection To the Rostral Subdivisimentioning
confidence: 89%
See 1 more Smart Citation
“…This suggests that a considerable proportion of the trigeminal primary nociceptive projection, especially from the intraoral structures, is directed to the relay nuclei located in the rostral subdivisions of the BSTC. This idea is supported by the fact that a large proportion of central projection of presumed primary nociceptors innvervating the tooth pulp is directed to rostral subdivisions of the BSTC (Arvidsson and Gobel, 1981;Westrum et al, 1981;Marfurt and Turner, 1984;Shigenaga et al, 1986bShigenaga et al, , 1989Takemura et al, 1991;Sugimoto and Takemura, 1993).…”
Section: Cgrp-ir Primary Afferent Projection To the Rostral Subdivisimentioning
confidence: 89%
“…In the former species, the PrV but not the Vo contains many projection neurons with ascending axons projecting to the contralateral nucleus ventralis posteromedialis (VPM) of the thalamus (Shigenaga et al, 1983(Shigenaga et al, , 1986b. Therefore, it may be that the principal relay nucleus involved in the intraoral nociception is the PrV in the cat.…”
Section: Cgrp-ir Primary Afferent Projection To the Rostral Subdivisimentioning
confidence: 96%
“…Both electrophysiological (Sessle and Greenwood, 1976;Sessle and Hu, 1981;Azerad et al, 1982;Sunada et al, 1990;Ro and Capra, 1994) and anatomical labeling (Mizuno, 1970;Woda et al, 1977;Burton and Craig, 1979;Matsushita et al, 1982;Shigenaga et al, 1986;Matthews et al, 1987Matthews et al, , 1989) studies performed in acute anesthetized cats have demonstrated that the rostral trigeminal sensory nuclear complex (TSNC) comprising, respectively, the nucleus oralis and the main sensory nucleus, contains a high density of TGT neurons. Recently, we have shown that the tooth pulp-evoked activity of rostral TSNC neurons is suppressed specifically during the behavioral state of active (AS) or REM sleep .…”
mentioning
confidence: 99%
“…Regarding projections of primary afferents to the Vo.r and Vo.dm, we have reported that the lower and upper teeth are represented in a dorsoventral sequence (Shigenaga et al, 1986c), and projections from the anterior to posterior teeth are organized in a ventrolateral to dorsomedial sequence (Shigenaga et al, 1989b). The projections from lingual afferents in the Vo.r and Vo.dm are organized in a similar fashion to those of the lower teeth, but both terminal fields may overlap extensively.…”
Section: Somatotopic Organizationmentioning
confidence: 91%